The Utilization of a Fish Pump for Harvesting Shrimp from Tanks and Ponds - Cortney L. Ohs; Scott W. Grabe; R. LeRoy Creswell (EDIS)
Commercial shrimp farms located throughout the world utilize several techniques to harvest shrimp from ponds and raceways. Commonly, farmers drain their systems and collect shrimp in nets, mesh bags or baskets as water passes through the drain. Other methods for partial harvest include cast netting or trapping the shrimp as water exits the pond gates during receding tides. Recently, modified mechanical pumps have proven to be very effective at harvesting shrimp from ponds and raceways. This document is FA123, one of a series of the Fisheries and Aquatic Sciences Department, UF/IFAS Extension. Original publication date February 2006.